1958
DOI: 10.1037/h0044102
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of a learning set by normal and mentally retarded children.

Abstract: A survey of the literature indicates that extensive studies of the learning process with mentally retarded children have been extremely rare. The purpose of the present study was to determine the applicability of discrimination-learning methodology, originally described by Harlow (3), to the study of learning in normal and mentally retarded children. Specifically, group differences in the acquisition of an object-quality discrimination learning set were studied. Also included in this study was an empirical ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

1959
1959
1990
1990

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 2 publications
2
19
0
Order By: Relevance
“…In comparing the learning-set performances of normal and educable children, Kaufman and Peterson (56) observed that normal children made more correct responses than retarded children on 48 object-quality problems, a significantly greater percentage of stimulus-perseveration errors being made by the retarded group (which did not include clinical types such as Mongoloids).…”
Section: Learningmentioning
confidence: 97%
“…In comparing the learning-set performances of normal and educable children, Kaufman and Peterson (56) observed that normal children made more correct responses than retarded children on 48 object-quality problems, a significantly greater percentage of stimulus-perseveration errors being made by the retarded group (which did not include clinical types such as Mongoloids).…”
Section: Learningmentioning
confidence: 97%
“…As noted above, previously HP monkeys were also found to repeat incorrect object choices in discrimination tasks. Stimulus perseveration has also been noted to characterize mentally retarded humans in learning set tasks (Kaufman & Peterson, 1958, 1965).…”
Section: Types Of Responsesmentioning
confidence: 99%
“…These investigations found superior response performances in both groups following failure on trial one, than following comparable success (House and Zeaman, 1958). However, on the same ta.sk (1958) and in a conditionaldiscrimination problem, Kaufman and Peterson (1965) foimd human retardates exhibiting more stimultis-perseveration errors (perseverating with the incorrect stimulus after a loss) than normals but no differences in the emission of response-shift errors.Where outcome is uncertain, Schusterman (1964) reports that severe mental retardates are more likely to make a ehoice based upon the outcome and the choice of the preceding trial, persisting less with a previously unsuccessful choice than less severe retardates or normals in a two-choice problem. Retardates, on the other hand, were found to be more stereotyped in an insolulile mtiltlple-choice task (Goulet and Barclay, 1967) and to perseverate more and alternate less in a complex binary-choice guessing game {Gerjuoy and Winters, 1966).…”
mentioning
confidence: 95%
“…These investigations found superior response performances in both groups following failure on trial one, than following comparable success (House and Zeaman, 1958). However, on the same ta.sk (1958) and in a conditionaldiscrimination problem, Kaufman and Peterson (1965) foimd human retardates exhibiting more stimultis-perseveration errors (perseverating with the incorrect stimulus after a loss) than normals but no differences in the emission of response-shift errors.…”
mentioning
confidence: 95%